THE NOVEL BY M. DOCHYNETS «THE VICAR. THE CONFESSION ON THE SPIRIT PASS» AS A MEDIA CULTURAL STRATEGY OF THE AUTHOR - Kovpik, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article focuses on the text polyfunctionality of the artistic work by M. Dochynets. The text of the novel "The Vicar. The Confession on the Spirit Pass" demonstrates the high level of author’s media culture. The author uses an interesting and original system of meanings and and additional to present the life realities of the main character. This paper shows the attempt to decode the system of meanings contained in the text of the novel, which contribute to the formation of qualitatively new knowledge about the world.